The Global Trend of Augmented Reality-Based Learning and Its Impact on Students' Academic Ability: A Meta-Analysis - Tamur, Maximus; Tommy Tanu Wijaya; Makur, Alberta P; Wibisono, Yudi; Pantaleon, Kristianus Viktor (Hipotenusa: Journal of Mathematical Society, 2024)
Today, there are many studies available in the literature that test the effectiveness of using augmented reality (AR). However, these studies provide varying results. In this regard, a meta-analysis is needed to examine the overall effect of all studies that question the influence of Augmented Reality-Based Learning (ARBL) on students' academic ability. Then, moderator variables need to be investigated to consider their implications. Data were examined from the Scopus and Google Scholar databases using the Publish or Perish application between 2016 and 2023. Data screening resulted in 69 independent groups of 32 eligible primary studies with 2659 subjects. Population estimation was based on a random effects model, and Comprehensive Meta-Analysis (CMA) was used as a calculation tool. The study's results provided an overall effect size of 0.81 (large effect). This shows that ARBL greatly affects students' academic ability, so its application must be considered. Of all the moderator variables analyzed, year of study, educational level differences, and subject matter were associated with differences in effect sizes in the main study. Thus, these three variables need to be considered in educational settings related to the development and implementation of ARBL in the future. Several new findings and research gaps are discussed and will help teachers, lecturers, and practitioners fill them in the future.